Case report: Manual carbon hemoperfusion for the treatment of meloxicam toxicity in a cat and suspected ibuprofen toxicity in a dog - Haire, Lauren E.; Vitalo, Amber D.; Gonçalves, Ronald P.; Lanaux, Travis M. (Frontiers in Veterinary Science, 2024)
Extracorporeal blood purification (ECBP) has become a popular treatment option for non-steroidal anti-inflammatory drug (NSAID) toxicity in small animals. However, challenges arise when using ECBP for small dogs and cats because the priming volume required by most machine-based ECBP platforms might be excessive, leading to cardiovascular instability if a blood prime is not used. This report describes the successful use of manual carbon hemoperfusion (MCHP) to reduce plasma meloxicam levels in a cat following an inadvertent overdose and its use in a dog following suspected ibuprofen ingestion. In both animals, MCHP reduced the circuit volume needed for ECBP from 125 mL with a machine-based therapeutic plasma exchange or 104 mL with an in-series carbon hemoperfusion on an intermittent hemodialysis platform to just 40–50 mL. In the cat, MCHP reduced plasma meloxicam levels by 44%, and in both animals, the use of MCHP in these pets was well-tolerated and safe. Due to pre-existing anemia, the cat required a blood transfusion but the dog did not. MCHP is technically simple and can be performed at any hospital with access to carbon filters and blood bank resources. This technique may represent a reasonable alternative to treat NSAID toxicities in animals that are too small for conventional extracorporeal decontamination methods using either machine-based platforms without using a blood prime or in locations where these machines are unavailable.